A Reactionary History? Reflections on the De-Democratization of the Past in the “Trump Era” United States - Lima de Avila, Arthur (História da Historiografia: International Journal of Theory and History of Historiography, 2025)
The present text aims to propose a few hypotheses about the current de-democratization of the past in the United States of the Trump Age, from the standpoint of a case study of anti-Critical Race Theory (CRT) laws approved by the Republican Party in a series of states and their assault on the honest judgment of the US history of slavery and racial violence. The text concludes that this assault is part of a larger process of political de-democratization that aims to, among other things, redefine the links between history and the polis in order to legitimize the “exit from democracy” currently underway in the country.